Relationship Between Smartphone Addiction and Sleep Disturbance in School Age Children - Muhamad Nurul Faizin; Eka Wahyuningrum; Andri Kenti Gayatina (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2021)
Sleep disturbances in school children result disrupted daytime function. The prevalence of sleep disturbances ranged from 25.1% - 44.8%. One of the causes of children's sleep disorders is the use of gadgets or smartphones. However, the research results convey things that are still pros and cons. This study aims to know the relationship between smartphone addiction and sleep disturbances in school-age children. This research is a quantitative research with a cross sectional study approach. The sampling technique in this study was consecutive sampling with a total sample of 165 children. Smartphone addiction data was measured using a modified Indonesian version of the smartphone addiction scale-short version (SAS-SV) questionnaire, and sleep disturbance data was measured using the sleep disturbance scale for children (SDSC) questionnaire. Data analysis used chi-square test with 95% confidence level. The result showed that 47.9% of children experienced addiction on average above, 31.5% of children had sleep disorders and chi-square test obtained p value of 0.001. The conclusion showed that there was significant relationship between smartphone addiction and sleep disorders in school-age children.